Maternal hemoglobin concentrations across pregnancy and maternal and child health: a systematic review and meta-analysis - Young, Melissa F.; Oaks, Brietta M.; Tandon, Sonia; Martorell, Reynaldo; Dewey, Kathryn G.; Wendt, Amanda (Annals of the New York Academy of Sciences, 2019)
Maternal anemia is a well-recognized global health problem; however, there remain questions on specific hemoglobin (Hb) thresholds that predict health risk or protection for mother and child. We conducted a systematic review and meta-analysis to examine the associations of maternal Hb concentrations with a range of maternal and infant health outcomes, accounting for the timing of measurement (preconception, and first, second, and third trimesters), etiology of anemia, and cutoff category. The systematic review included 272 studies and the meta-analysis included 95 studies. Low maternal Hb (<110 g/L) was associated with poor birth outcomes (low birth weight, preterm birth, small-for-gestational-age (SGA), stillbirth, and perinatal and neonatal mortality) and adverse maternal outcomes (postpartum hemorrhage, preeclampsia, and blood transfusion). High maternal Hb (>130 g/L) was associated with increased odds of SGA, stillbirth, preeclampsia, and gestational diabetes. Relationships varied by the timing of measurement and cutoff category (stronger associations with lower cutoffs); limited data were available on anemia etiology. There were insufficient data for other maternal outcomes and long-term child health outcomes. Current data are insufficient for determining if revisions to current Hb cutoffs are required. Pooled high-quality individual-level data analyses, as well as prospective cohort studies, would be valuable to inform the reevaluation of Hb cutoffs.
Gesehen am 29.04.2020